Iatrogenic profound hypoalphalipoproteinaemia: an unrecognised cause of very low HDL cholesterol. Issue 838 (August 1995) - Murphy, M. J.; Duncan, A.; Vallance, B. D.; Packard, C. J.; O'Reilly, D. S.
Abstract : A significant reduction in plasma high density lipoprotein (HDL) cholesterol is a recognised consequence of treatment with probucol. By contrast, fibrate therapy in general has the opposite effect. We report two cases where the combination of probucol and a fibrate led to profoundly reduced plasma levels of HDL cholesterol associated with very low levels of apolipoprotein A-I (apoA-I). In the first, bezafibrate was added to probucol, and in the second, probucol added to a combination of simvastatin and fenofibrate. In both cases, plasma levels of HDL and apoA-I returned towards normal after discontinuation of one or both drugs, indicating that the reduction was reversible.